2022
DOI: 10.3390/life13010021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Probiotic Properties of Lacticaseibacillus paracasei L2 Isolated from a Traditional Fermented Food “Lben”

Abstract: Lben is a dairy fermented food that is largely consumed in Tunisia for its numerous health benefits that are related to the existence of probiotics. Lactic Acid Bacteria (LAB) are well known for their beneficial probiotic properties for humans, especially when administered in adequate amounts. The aim of this study was to isolate and investigate the probiotics properties of Lacticaseibacillus paracasei L2 from Lben. The isolated strain was identified by 16S r-RNA gene sequences and MALDI- TOF MS. To evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Screening of microorganisms from traditional fermented foods has been a powerful tool to obtain new strains for industrial use, providing better fermentation properties and/or desirable health benefits (M'hamed et al., 2022; Trivedi et al., 2022). From a naturally fermented fruit beverage, this work isolated and identified a Lactiplantibacillus plantarum strain BXM2, which could be beneficial and genetically stable for industrial food fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of microorganisms from traditional fermented foods has been a powerful tool to obtain new strains for industrial use, providing better fermentation properties and/or desirable health benefits (M'hamed et al., 2022; Trivedi et al., 2022). From a naturally fermented fruit beverage, this work isolated and identified a Lactiplantibacillus plantarum strain BXM2, which could be beneficial and genetically stable for industrial food fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…L. paracasei AD22 showed good probiotic properties, showing remarkable growth in the acidic pH 2 milieu. Kumar et al and M'hamed et al reported that no growth occurred due to the incubation of isolated lactobacilli at pH 2 [37,38]. Adaptation to bile salts is affected by changes in carbohydrate fermentation and glycosidase activity [39], exopolysaccharide production [40], the composition of membrane proteins and fatty acids [41], and human intestinal mucosa and the inhibition of the attachment of pathogens [42].…”
Section: Evaluation Of L Paracasei Ad22 In Terms Of In Vitro Physiolo...mentioning
confidence: 99%
“…The probiotic properties of all 16 isolates were evaluated, including their ability to tolerate varying levels of temperature change, pH change, NaCl concentration, Bile salt tolerance, and antimicrobial properties (Dabiré et al, 2022;M'Hamed et al, 2022). Figure 1A displays the temperature study results, where the ability of each isolate to grow in MRS broth at 10, 21, 37, and 42 • C was tested.…”
Section: Study the Probiotic Attributes Of Microorganismsmentioning
confidence: 99%
“…Probiotics can cure various health conditions, such as inflammatory bowel disease, irritable bowel syndrome, constipation, antibiotic-associated diarrhea, acute diarrhea, allergy-related diseases, hypertension, and diabetes. However, for probiotic strains to function appropriately, they must exhibit certain beneficial qualities such as tolerance to gastrointestinal illnesses, adhesion to epithelial cells, ability to absorb cholesterol, hydrolysis of bile salts, safety against virulence genes, non-hemolytic activity, antibiotic sensitivity, antibacterial properties, and viability during fermentation and storage processes (A'inurrofiqin et al, 2022;M'Hamed et al, 2022). Moreover, it is preferable for probiotic strains to have industrial important characteristics like tolerance to heat treatment, mainly spray drying, and exopolysaccharide (EPS) production, which can benefit consumers as non-digestible fiber or food flavor.…”
Section: Introductionmentioning
confidence: 99%